(3ceGd GdaQMI aj OaY GdSehe hMaX GdUMIs - (3GdbhUhfj , TeS GdOjf eMeO Hf eMeO Hf eMeO Hf HOQ GdOjf GdbhUhfj,J (B931 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdMdje GdeOHQ GdMcje Pi GdbhI hGdSdWGf GdOGFe GdHGbi hcd ef YdjgG aGf s
(3BNQgG (B:s
(3BNQ GdehLhO efgG bhdg hEPG MQc GdfUGH ai GdWYGe GdeSehe cSQ ShQI GdSe hVQQg ai GdhbJ hGdMGd hEPG Ccdg EfSGf s
(3fSNI NRGFfjI cJHJ HQSe NRGfI GdSdWGf CHj GdfUQ bGfUhI GdZhQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B260s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1509s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdWHs